2001
DOI: 10.1161/01.cir.103.11.1529
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Aortic Calcific Deposits Are an Important Predictor of Vascular Morbidity and Mortality

Abstract: AAC deposits, detected by lateral lumbar radiograms, are a marker of subclinical atherosclerotic disease and an independent predictor of subsequent vascular morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
427
2
9

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(460 citation statements)
references
References 30 publications
8
427
2
9
Order By: Relevance
“…Again, the positive relationship of AAC with vascular disease was not a simple consequence of different lifestyle behaviours, increased levels of standard risk factors or decreased use of medications with potential beneficial vascular effects. As the current study was able to quantitate more precisely the extent of abdominal calcium and to determine the relationship of increasing burdens of AAC with CVD, these data add substantially to earlier reports that calcium seen in the abdominal aorta on standard radiographs may be a useful predictor of clinical CVD [26][27][28]. Moreover, this study demonstrates that AAC is also related to vascular disease in patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 72%
“…Again, the positive relationship of AAC with vascular disease was not a simple consequence of different lifestyle behaviours, increased levels of standard risk factors or decreased use of medications with potential beneficial vascular effects. As the current study was able to quantitate more precisely the extent of abdominal calcium and to determine the relationship of increasing burdens of AAC with CVD, these data add substantially to earlier reports that calcium seen in the abdominal aorta on standard radiographs may be a useful predictor of clinical CVD [26][27][28]. Moreover, this study demonstrates that AAC is also related to vascular disease in patients with type 2 diabetes.…”
Section: Discussionsupporting
confidence: 72%
“…(16)(17)(18)(19)(20)(21) Recently, we and others have reported that AAC can be measured on vertebral morphometric images obtained by dual-energy X-ray absorptiometry (DXA) and that the presence of AAC independently predicted incident MI, stroke, and cardiovascular events, even after adjusting for traditional cardiovascular risk factors. (22)(23)(24)(25) AAC also has been inversely associated with BMD in many studies.…”
Section: Introductionmentioning
confidence: 99%
“…Arterial disease associated with ESRD is characterized by a high degree of intimal as well as medial calcification. Calcification has been shown to affect vascular elasticity (3) and mortality (4,5). The presence of calcification in patients with ESRD has been associated with increased stiffness of large capacity, elastic-type arteries like the aorta and the common carotid artery.…”
mentioning
confidence: 99%